Perancangan Konsep Adaptasi Permainan Tradisional Bas-Basan Sepur dalam Permainan Digital "Amukti Palapa" - Khamadi Khamadi; Riama M. Sihombing; Hafiz Aziz Ahmad (Wimba : Jurnal Komunikasi Visual, 2013)
Bas-basan Sepur is a traditional board game, commonly played by teenagers that challenge the strategy skills of two players. Like the other traditional games, the existence of bas-basan Sepur is forgotten due to disconnection of cultural inheritance from parents to their children and also the loss of childrenâs playground and play time. Children nowadays are more interested in modern digital games such as video games and mobile games. Accordingly, the effort to reintroduce bas-basan Sepur into a digital game design is quite effective to attract children. The game design includes the process of data collecting, data analyzing, and game designing. With ATUMICS methode (Artefact, Technology, Utility, Material, Icon, Concept, Shape), data on bas-basan Sepur were analyzed to obtain the components of traditional culture, which can be transformed into a digital game. In the process of designing digital games, bas-basan Sepur will be combined with historical narrative, Amukti Palapa - the events of Nusantara unification under the influence of the Majapahit kingdom - to provide the motivation of playing which is more attractive to players. Data on Amukti Palapa were analyzed based on chronological events, places, and characters as the basic level design and visualization of the characters and the game environment assets. As a result, an adventure-board digital game of bas-basan Sepur that brought the chronological story of Amukti Palapa.